Drop-weight impact test on an integrated composite sandwich panel of aluminum honeycomb and epoxy resin. Issue 12 (22nd May 2017) - Cheng, Shuliang; Xiao, Bo; Zhao, Xuya; Xin, Yajun; Li, Huijian
Abstract: Abstract : In this paper, drop-weight impact test was carried out on an integrated composite sandwich panel of aluminum honeycomb and epoxy resin to investigate its failure modes and typical force–displacement curves, and the influences of different parameters on plateau phase duration time, nominal stress, and energy absorption capacity were analyzed. Dynamic impact test results indicated that this integrated composite sandwich panel had good integrality, stability, and energy absorption capacity. The force–displacement curves of flat-bottom impactor and gradual impactor respectively had seven and five phases. Impact velocity, impactor shape, and specimen thickness had significant influences on the plateau phase duration time, nominal stress, and energy absorption capacity of the composite panel. It can be found from our results that the mechanical properties of the integrated composite sandwich panel were superior to those of traditional sandwich panels.